Recognition of β–Calcineurin by the Domains of Calmodulin: Thermodynamic and Structural Evidence for Distinct Roles - O’Donnell, Susan E. (2010)
Calcineurin (CaN, PP2B, PPP3), a heterodimeric Ca(2+)-calmodulin-dependent Ser/Thr phosphatase, regulates swimming in Paramecia, stress responses in yeast, and T-cell activation and cardiac hypertrophy in humans. Calcium binding to CaN(B) (the regulatory subunit) triggers conformational change in CaN(A) (the catalytic subunit). Two isoforms of CaN(A) (α, β) are both abundant in brain and heart and activated by calcium-saturated calmodulin (CaM). The individual contribution of each domain of CaM to regulation of calcineurin is not known. Hydrodynamic analyses of (Ca(2+))(4)-CaM(1-148) bound to βCaNp, a peptide representing its CaM-binding domain, indicated a 1:1 stoichiometry. βCaNp binding to CaM increased the affinity of calcium for the N- and C-domains equally, thus preserving intrinsic domain differences, and the preference of calcium for sites III and IV. The equilibrium constants for individual calcium-saturated CaM domains dissociating from βCaNp were ~1 μM. A limiting K(d) ≤ 1 nM was measured directly for full-length CaM, while thermodynamic linkage analysis indicated that it was approximately 1 pM. βCaNp binding to (15)N-(Ca(2+))(4)-CaM(1-148) monitored by (15)N/(1)HN HSQC NMR showed that association perturbed the N-domain of CaM more than its C-domain. NMR resonance assignments of CaM and βCaNp, and interpretation of intermolecular NOEs observed in the (13)C-edited and (12)C-(14)N-filtered 3D NOESY spectrum indicated anti-parallel binding. The sole aromatic residue (Phe) located near the βCaNp C-terminus was in close contact with several residues of the N-domain of CaM outside the hydrophobic cleft. These structural and thermodynamic properties would permit the domains of CaM to have distinct physiological roles in regulating activation of βCaN.